Determinants of Stunting in Children Under Five in Rural Areas - Eva Purwita (Institute of Computer Science (IOCS), 2022)
Stunting is a major nutritional problem that will have an impact on social and economic life in society. Stunting is prone to occur in toddlers. Stunting toddlers tend to find it difficult to achieve optimal growth and development potential, both physically and psychomotor. This study is a systematic review using online databases, namely Sciencedirect, ProQuest, Scopus, and Google Scholar. The keywords used are stunting, toddlers, rural areas and their impact. The purpose of the systematic review is to analyze the factors that influence the incidence of stunting in children under five in rural areas. The results of the review show that the factors that influence the occurrence of stunting in children under five in rural areas are mother's education, family income, mother's knowledge of nutrition, exclusive breastfeeding, age of giving complementary feeding, levels of zinc and iron adequacy, history of infectious diseases. and genetic factors. However, for the mother's employment status, the number of family members, immunization status, energy adequacy level, and LBW status did not affect the occurrence of stunting. The factor that most influences the occurrence of stunting in children under five in rural areas is the level of zinc adequacy. It is recommended for the community to be active in outreach activities and other health activities carried out in order to improve health status and for mothers should routinely carry out weighing at the nearest posyandu so that the growth and development of children can be monitored and can be handled immediately if problems are found in the child's growth and development.